(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Abstract – Now days because of increasing road traffic in big cities resulting into the traffic jam problems, accidents and more importantly pollution. Since from last two decades, traffic related problems gaining interest of many researchers on behalf engineering as well as theoretical analysis. The efficient traffic control methods are having direct impact of vehicular emission controls. For measuring the exhaust emission as well as assessing the pollution control effect by using the practical and simple technique, a model is based on the relationship between traffic flow and vehicle exhaust emission under a certain level of road capacity constraints. There are many recent studies presented on relationship between traffic control methods and vehicular emission by using simulators. The ultimate goal of traffic control method is to minimize the excessive emissions and fuel consumptions in order to prevent the pollution in cities. This can be achieved by successful study on relationship between the traffic control and emission control systems. The models like VISSIM, VISGAOST, and CMEM were linked to optimize signal timings and minimize fuel consumption and CO2 emissions in literature. This models were adopted the study among traffic control and emission control systems. These models are designed independently and not integrated with traffic control models and emission control frameworks. And hence limitations we identified from literature study is that there is no study presented so far for integrating the recent microscopic tools for finding the optimal signal timings using which the minimization of emissions and fuel consumptions done. The recent studies do not have enough research presented so far over how to study the relationship between emission control and traffic control systems. Therefore the aim of this research work is to present the efficient framework to study the relationship between traffic control model and emission control by categorizing the solution into two parts such as first is to present the study on relationship between emission control and isolated intersection, whereas second is to present the study on coordinate intersection and emission control with goal of minimizing the fuel consumption. The analytical study conducted on both parts, in first part ten different methods evaluated related to isolated intersection and in second part different methods coordinate intersections. From the analytical results for first study, method 3 is showing efficient performance for delay and emission reduction. For second study, method 2 is showing the efficient performance for delay and emission reduction.